Phthalates in the environment of China: A scoping review of distribution, anthropogenic impact, and degradation based on meta-analysis - Zhigang Cui; Ce Shi; Lanting Zha; Jiaman Liu; Yinchu Guo; Xiaohan Li; Enjiao Zhang; Zhihua Yin (Ecotoxicology and Environmental Safety)
Phthalates (PAEs) are a group of endocrine-disrupting environmental chemicals (EEDs) that pose significant risks to human health. PAEs are widespread in various environmental media, including air, dust, water, and soil, and are subject to both horizontal and vertical migration. Human activities significantly influence the distribution of PAEs, yet current research on this relationship remains limited. In this study, we first describe the hot issues of PAEs in the environment through bibliometrics, and then review published related studies. We outline the global distribution of PAEs in different media and conducted a comparative analysis of their composition. Principal component analysis (PCA) revealed PAEs differences in environmental mediums and geographic locations. Correlation analysis between PAEs composition and human activities in China further demonstrated that PAE concentrations were closely linked to agricultural and industrial activities. We also discussed the biodegradation and abiotic degradation of PAEs, finding that bacteria play a crucial role in their degradation in soil. This study aims to assess the distribution, transfer, impact, and degradation of PAEs, providing insights for the prevention and remediation of PAE pollution.